Guidance Information Processing Methods in Airborne Optical Imaging Seeker - Zhang, Tianxu; Wang, Yuehuan; Zhong, Sheng; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book covers all main aspects of guidance information processing technologies for airborne optical imaging seekers, including theoretical models; image pre-processing; automatic target detection, recognition and tracking; and embedded real-time processing systems. The book is divided into three major sections: firstly, a theoretical model for optical-seeker information processing is introduced; then information processing methods are presented, including target modeling, online image pre-processing, typical surface fixed-target detection and recognition, and moving-target detection and recognition; lastly, embedded real-time processing systems are introduced, including new system architectures, image processing ASIC/SoC design, embedded real-time operating systems, system implementation aspects, and system testing and evaluation technologies. The book offers a unique and valuable resource, helping readers understand both fundamental and advanced information processing technologiesemployed in airborne optical imaging seekers. .
Introduction -- A Theoretical Model of Optical Seeker Information Processing -- Spatial Characteristics and Relationship of Platform, Targets and Background -- Reducing Disturbance Effects on Optical Imaging Platform -- Optical Imaging Seeker Processing Approach to Earth Surface Fixed Targets -- Optical Imaging Seeker Processing Approach to Moving Targets -- Design and Implementation of Real-Time Processing Systems -- Optical Imaging Seeker Information Simulation and Performance Evaluation.
Keywords: Signal processing; Computer vision; Lasers; Signal, Speech and Image Processing; Computer Vision; Laser